Investigation of the risk factors associated with the failure of hepatitis B vaccination of neonates in Yunnan province, China. (December 2018) - Wang, Feng; Kang, Wenyu; Zhou, Wenting; Su, Qiudong; Bi, Shengli; Qiu, Feng; Li, Qiongfen
Highlights: A large number of individuals was subjected to the seroprevalence investigation. Propensity score and GLMMs were applied to the case-control study. It is difficult to conduct a seroprevalence study in a remote area of mainland China. Abstract: Objective: This study aimed to investigate HBsAg positive rates and risk factors of HBV infection among the children less than 15 years old in Yunnan province, a remote southwest part of mainland China. Methods: Multi-stage sampling was used to randomly select study subjects from 9, 360, 000 individuals. Hepatitis B vaccine inoculation rate and HBsAg positive rate were investigated, and then propensity score and generalized linear mixed model (GLMMs) were applied to the case-control study. Results: The average HBsAg positive rate was 1.81%, with 1.2% in urban areas and 2.4% in rural areas. Rate of first-dose-in-time in urban areas was 77.7%, obviously higher than 49.5% in rural areas ( χ 2 = 2811.71, P < 0.01). Similarly, 3-dose completion coverage rate in urban areas was 93.7%, also higher than 79.0% in rural areas ( χ 2 = 1561.43, P < 0.01). Maternal HBeAg positivity and HBsAg positivity were proved to be the main risk factors of children with HBV infection. Moreover, paternal HBeAg positivity, paternal HBsAg positivity, the absence and unknown status of HBV vaccine inoculation were risk factors of children with HBV infection as well. Conclusion: It was very important to improve the HBV vaccine inoculation rates. Delivering babies in hospital and timely inoculation with HBV vaccine were efficient ways to prevent HBV vertical transmission.